2017
DOI: 10.1186/s11671-017-1833-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Characterization, and Bioactivities Evaluation of Silver and Gold Nanoparticles Mediated by the Roots of Chinese Herbal Angelica pubescens Maxim

Abstract: A facile synthesis and biological applications of silver (DH-AgNps) and gold nanoparticles (DH-AuNps) mediated by the aqueous extract of Angelicae Pubescentis Radix (Du Huo) are explored. Du Huo is a medicinal root belonging to Angelica pubescens Maxim which possesses anti-inflammatory, analgesic, and antioxidant properties. The absorption spectra of nanoparticles in varying root extract and metal ion concentration, pH, reaction temperatures, and time were recorded by ultraviolet–visible (UV-Vis) spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 33 publications
4
54
0
3
Order By: Relevance
“…Similarly, XRD spectra of Cs-AuNps (Figure 2(b)) and Cs-AgNps (Figure 2(e)) demonstrated identical diffraction peaks. Multiple negligible diffraction peaks in Figure 2(e) were present indicating the formation of bio-organic impurities in Cs-AgNps [5]. No artificial diffraction peaks due to crystallographic impurities were evident in Cs-AuNps, indicating pure gold metal.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, XRD spectra of Cs-AuNps (Figure 2(b)) and Cs-AgNps (Figure 2(e)) demonstrated identical diffraction peaks. Multiple negligible diffraction peaks in Figure 2(e) were present indicating the formation of bio-organic impurities in Cs-AgNps [5]. No artificial diffraction peaks due to crystallographic impurities were evident in Cs-AuNps, indicating pure gold metal.…”
Section: Resultsmentioning
confidence: 97%
“…malic acid, tartaric acid, limonin, vitamin C, tannin), which are the major phytochemicals of C. sinensis fruit [2][3][4]. Bioreduction methods based on plants [1,5,6], fungi [7] and bacteria [8] are more benefiting as the usage of harmless solvent, non-toxic reducing agents and ecofriendly materials reduce the risks of biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that AO contains antioxidants that can catalyze ROS into O 2 and H 2 O. [ ][ ] Hence, AO possesses both antioxidant and anti‐inflammatory effects, which are crucial to its anti‐photoaging effect.…”
Section: Resultsmentioning
confidence: 99%
“…The average crystallite size was 12.48 nm. 48 Generally, by augmenting the concentration of AgNO 3 , the production of AgNPs increases 46 and the color of the solution intensifies, because aggregation of silver ions occurs and larger nanoparticles are obtained. 14 In the case of AgNPs from Solanum trilobatum using 1 mM AgNO 3 , monodisperse nanoparticles were formed without aggregation.…”
Section: Concentration Of Silver Saltmentioning
confidence: 99%